CSF and IT-BSC Integration in IS/IT Strategic Management: A Conceptual Model from a Systematic Literature Review - Salsabila Nurisma Nadia Salma; Sholiq (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
In the era of digital transformation, aligning Information Systems and Information Technology (IS/IT) strategies with organizational objectives remains a critical challenge in strategic management. Previous studies have examined Critical Success Factors (CSFs) in Strategic Information Systems Planning (SISP) and the IT Balanced Scorecard (IT-BSC) as a performance measurement framework. However, these approaches are often discussed separately, while their integration within a unified IS/IT strategic management perspective remains limited. This study conducts a Systematic Literature Review (SLR) using the PRISMA approach to examine the roles of CSFs and IT-BSC in IS/IT strategic management. A total of 27 articles published between 2020 and January 2026 were selected from multiple academic databases. The findings show that CSFs primarily support the identification and prioritization of IS/IT strategic initiatives through the SISP process, while IT-BSC is widely used to measure performance, assess alignment, and support structured strategic improvement. The review further indicates that CSFs and IT-BSC should be understood as complementary components. Based on the literature synthesis, this study proposes a conceptual CSF and IT-BSC integration model that links strategic objectives, CSFs, IS/IT needs, IT-BSC perspectives, and performance evaluation. The proposed model is literature derived and has not yet been empirically validated. Therefore, it should be understood as a conceptual basis for future empirical testing and further development in IS/IT strategic management.